1996
DOI: 10.1152/jappl.1996.80.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for contribution of effector organ cellular responses to the biphasic dynamics of heat acclimation

Abstract: The involvement of cellular processes in the biphasic dynamics of heat acclimation was studied. Key steps in the cholinergic signal transduction pathway for water secretion were measured in the submaxillary gland of acclimating [2-day short-term heat acclimation (STHA) and 30-day long-term heat acclimation (LTHA) at 34 degrees C] or acute heat-stressed (2 h at 40 degrees C) rats in vitro. Both the carbamylcholine (CCh)-induced maximal fractional rate and the total 86Rb+ efflux, reflecting K+ efflux and water t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 0 publications
1
48
0
Order By: Relevance
“…There is evidence for a temporal biphasic pattern of heat acclimation: short-term and long-term heat acclimations (STHA and LTHA, respectively;Horowitz et al, 1996;Hahn, 1999;Horowitz, 2002). STHA is the phase in which changes are initiated within cellular signalling pathways (Horowitz et al, 1996) leading to disturbances in cellular homeostasis and begins to reprogram cells to survive the deleterious effects of heat stress (Horowitz, 2001).…”
Section: Heat Stress Critical Temperatures and Bioclimatic Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence for a temporal biphasic pattern of heat acclimation: short-term and long-term heat acclimations (STHA and LTHA, respectively;Horowitz et al, 1996;Hahn, 1999;Horowitz, 2002). STHA is the phase in which changes are initiated within cellular signalling pathways (Horowitz et al, 1996) leading to disturbances in cellular homeostasis and begins to reprogram cells to survive the deleterious effects of heat stress (Horowitz, 2001).…”
Section: Heat Stress Critical Temperatures and Bioclimatic Indicesmentioning
confidence: 99%
“…In addition, acclimatory responses possess a hormonal link in the pathway from the central nervous system to the effector cells, and usually alter the response of effector cells or organs to an environmental challenge. The main effect of these acclimatory responses is to coordinate metabolism to achieve a new equilibrium that could be considered as a new physiological state.There is evidence for a temporal biphasic pattern of heat acclimation: short-term and long-term heat acclimations (STHA and LTHA, respectively;Horowitz et al, 1996;Hahn, 1999;Horowitz, 2002). STHA is the phase in which changes are initiated within cellular signalling pathways (Horowitz et al, 1996) leading to disturbances in cellular homeostasis and begins to reprogram cells to survive the deleterious effects of heat stress (Horowitz, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is hypothesised that the appearance of a lower sweat rate in such indigenes is an example of thermoregulatory habituation (negative phenotypic adaptation), and is indicative of a superior overall heat adaptation, possibly representing an extension of the two adaptation stages identified by Horowitz et al (1996). In fact, a large number of investigators have reported lower sweat responses in indigenous people from several continents, in comparison with Caucasians exposed to an equivalent heat stress: Thompson (1954: Negroid); Edholm et al (1964: Indians); McCance and Purohit (1969: Indians and Negroid); Fox et al (1974: New Guineans) McCance et al (1974: Bedouin); Samueloff (1987: Indians); Duncan and Horvath (1988: tropical Asians).…”
Section: Article In Pressmentioning
confidence: 99%
“…It is known that heat adaptation is manifested at various levels throughout the body; i.e. the subcellular, cellular, organ, and systemic levels (Adam et al, 1960;Horowitz et al, 1996). It has been proposed that changes in cutaneous thermal sensitivity are induced by alterations in the structure and function of cutaneous thermal receptors (Brück, 1986), such as decreases in the number or size of warm/cold spots in the skin or changes in the neurotransmission speed of nerves (Meliala et al, 1999) and a reduced maximum firing activity of single cold responsive units (Hinckel and Schroder-Rosenstock, 1982).…”
Section: No Evidence Was Found For the Decaying Of The Cutaneous Thermentioning
confidence: 99%